Jenis-Jenis Ikan Indonesia yang Kritis dan Terancam Punah: The Indonesian Fish Species That Are Critical and Threatened - Andri Iskandar; M Muslim; Andri Hendriana; W Wiyoto (IPB University, 2020)
ABSTRACTIndonesia has a high diversity of fish species. Some fish species are critical and endangered. Information on Indonesian native and endemic fish species needs to be disseminated to the public. Such information is available in various sources and is generally in a foreign language. Therefore, the purpose of this research is to inventory and distribute information about several species of fish native to Indonesian public waters that need special attention because they are endangered and critically endangered. Species of fish, especially species that have been critically endangered, do not rule out turning into extinct in the wild (extinct in the wild). The decline in the status of the above from vulnerable (vulnerable) to endangered (endangered) and critical (critically endangered) or even become extinct in the wild (extinct in the wild) caused by various factors, including the existence of fisheries activities that tend to exploit natural resources without offset by conservation activities and increasing pollution of water conditions. With this information, it is expected to anticipate the extinction of these species. The study was conducted using the literature study method. Based on the search results, there were 22 endangered fish species and 15 critically endangered fish species. The Indonesian government has designated 20 protected fish species. Domestication of endangered and critical species is urgent to do, to prevent the extinction of these species. ABSTRAKIndonesia memiliki keanekaragaman spesies ikan yang tinggi. Beberapa spesies ikan sudah kritis dan terancam punah. Informasi jenis-jenis ikan asli dan endemik Indonesia perlu diserbarluaskan ke masyarakat. Informasi tersebut terdapat diberbagai sumber dan umumnya berbahasa asing. Oleh karena itu, tujuan penelitian ini adalah untuk menginventarisasi dan mendistribusikan informasi tentang beberapa spesies ikan asli penghuni perairan umum Indonesia yang perlu mendapat perhatian khusus karena berstatus terancam punah (endangered) dan kritis (critically endangered). Spesies-spesies ikan tersebut terutama spesies yang sudah berstatus kritis terancam punah, tidak menutup kemungkinan berubah menjadi punah di alam liar (extinct in the wild). Terjadinya penurunan status diatas dari rentan (vulnerable) ke terancam punah (endangered) dan kritis (critically endangered) atau bahkan menjadi punah di alam liar (extinctin the wild) disebabkan oleh berbagai macam faktor, diantaranya adanya kegiatan perikanan yang cenderung mengeksploitasi sumber daya alam tanpa diimbangi dengan kegiatan konservasi serta meningkatnya pencemaran terhadap kondisi perairan. Dengan adanya informasi ini diharapkan dapat melakukan antisipasi pencegahan kepunahan spesies tersebut. Penelitian dilakukan dengan metode studi literatur. Berdasarkan hasil penelusuran, diperoleh 22 spesies ikan yang terancam punah (endangered) dan 15 spesies ikan yang sudah kritis (critically endangered). Pemerintah Indonesia telah menetapkan 20 spesies ikan yang dilindungi. Domestikasi spesies-spesies yang terancam punah dan kritis sudah mendesak untuk dilakukan, untuk mencegah kepunahan spesies tersebut.